On the Use of CLIL at Lithuanian Schools - Janulienė, Aušra (Verbum, 2010)
The changing globalized world has brought a new generation of students with a new mindset who are particularly focused on learning by doing. Young people are used to traveling, going to international camps, mixing with foreigners studying at their schools, fighting online computer game battles in teams with their contemporaries abroad. While being involved in any of these activities, they pick up some English. Many English course books that students use in class are also constructed according to the task-based approach to language learning where they use English as a tool to solve problems, design brochures, plan their tourist routes, etc. Consequently, Content Integrated Language Learning (CLIL) with its focus on integration must look very natural and motivating for these students enabling them to achieve both content and language goals. On the other hand, teachers must also be familiar and ready to use CLIL as they are participating in projects and attending numerous continuous development seminars where CLIL is one of the popular topics. Moreover, during the recent decades quite a few school teachers of other subjects or primary classes have acquired English teacher’s qualification as a result of requalification programs making them ideal candidates to combine content and language in their teaching. The aim of the article is to reveal the current situation regarding the use of CLIL. In order to achieve the aim a survey among Šakiai district teachers was carried out to find out their involvement in CLIL as well as problems they face. The research has shown that the majority of educators in the district are aware of CLIL and more than 30% of them have not only read related literature or discussed the issue with colleagues but have also participated in certain seminars, lectures and courses, some even abroad. Despite that, the educators still feel the lack of training, knowledge and competence to use it in their everyday work. The article presents a detailed discussion of the findings.
Keywords: foreign language teaching; CLIL; teacher training.